Characterization and Opportunities for the Improvement of Solid Waste at the educational institution, La Esperanza (Trujillo-Peru), 2019 - Veneros Urbina, Bilmia (2020)
The purpose of the research was to determine the characterization and opportunities for improvement of solid waste at the educational institution. The research is non-experimental, presented a transversal and descriptive design. The population and sample consisted of the waste generated by the students, teaching and administrative staff of the San José educational institution of the district of La Esperanza, province of Trujillo, region La Libertad, which represent a total of 1551 people. The measurement and characterization of waste was carried out taking into account the guide for the characterization of household solid waste, formulated by Kunitoshi Sakurai (1982). The opportunities for improvement were developed through a focus group and brain storning where the members of the educational community participated, and then be shown through a double entry matrix. The characterization of solid waste was determined and improvement opportunities were established that contribute to an adequate solid waste management of the educational institution, La Esperanza - La Libertad region. Solid waste was characterized, the solid residue with the highest percentage being paper with 25.56%, plastic with 16. 33% and fruit remains with 15.69%, while residues with a lower percentage such as metals with 2.08%, cardboardwith 5.26% and wood with 5.26%. Per capita production shows that each person can generate solid waste at a value of 65 grams for each member of the educational community. A matrix was developed where there are opportunities for improvement to reduce and properly manage solid waste generated in the EI “San José, La Esperanza - La Libertad region, highlighting, the environmental management policy, implementation of a composting plant, program of training and recycling, for this purpose, responsible and established times were determined.